Lung function defects in treated pulmonary tuberculosis patients. Issue 1 (January 2016) - Aggarwal, Deepak; KU, Vivek; Janmeja, Ashok K.
In their study, Amaral et al. [1] have nicely demonstrated the association of obstructive and restrictive lung function defects in patients with a past history of tuberculosis (TB). However, a few points regarding these tubercular sequelae need to be discussed in order for the results to be fully understood. Healed pulmonary TB often presents with residual lung function defects which may require further treatment http://ow.ly/TXfLm